Pelaksanaan Fungsi Pengawasan Dinas Lingkungan Hidup Kabupaten Pacitan Terhadap Pengelolaan Limbah B3 PLTU Sudimoro Di Kabupaten Pacitan - Oky Shiang Pradana; I Gusti Ayu Ketut Rachmi Handayani (Faculty of Law Universitas Sebelas Maret Surakarta, 2020)
This legal writing has the purpose to knowing the supervision by the Pacitan District Enviromental Services on Hazardous Waste Management at the PLTU Sudimoro in Pacitan Regency. This legal research is included in the type of empirical legal research that has character is descriptive and uses a qualitative approach. In this study the source of the data obtained is the primary data source, which is based on the results of direct interviews with related sources, namely the Pacitan District Enviromental Services. Apart from primary data, it is also based on secondary data with library research.Based on the results of the research that has been carried out, it can be concluded that the Environmental Service of Pacitan Regency in exercising its supervisory authority for hazardous waste management has run quite well and is in accordance with the applicable laws and regulations. In the supervision of the B3 waste management, PLTU Sudimoro that has been carried out has covered all the stages related to the supervision of hazardous waste management at the district / city level. However, in exercising the authority to supervise the management of B3 waste from PLTU Sudimoro by the Environmental Service of Pacitan Regency, several inhibiting factors were found, namely related to human resources, activity budget, geographical conditions, and limited operational vehicles.